Implementasi Manajemen Mutu Strategik pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Wajo - Andi Yuniarti; Faisal; Awalia Putri; Nur Rizki (Precise Journal of Economic, 2025)
The implementation of strategic quality management in zakat institutions is crucial for improving accountability, transparency, and the social impact of zakat fund management. This study aims to analyze the implementation of strategic quality management at the National Zakat Agency (BAZNAS) in Wajo Regency. A qualitative case study approach was used, with data collected through in-depth interviews with the Head of BAZNAS in Wajo Regency, observations, and document review. The results indicate that BAZNAS in Wajo Regency has adopted a strategic quality framework through planning based on the Strategic Plan and Work Plan (RKAT), the implementation of Standard Operating Procedures (SOPs), and a multi-layered monitoring and evaluation mechanism. The leadership acts as a motivator and facilitator using a participatory approach. Challenges faced primarily relate to the on-demand funding model and limited public understanding of zakat. Nevertheless, the implementation of strategic quality has strengthened organizational governance and increased public trust. This study recommends strengthening synergies with local governments and increasing zakat outreach to optimize BAZNAS's role in poverty alleviation